2015
DOI: 10.7883/yoken.jjid.2014.263
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence, Seroconversion, and Risk Factors for Toxoplasmosis among Pregnant Women in Taipei, Taiwan

Abstract: SUMMARY: Herein, we determined the seroprevalence, seroconversion, and risk factors associated with Toxoplasma gondii (T. gondii) infection among pregnant women in Taipei, Taiwan. Pregnant women attending antenatal consultation in a Taipei medical center were invited, and 104 women completed a self-administered structured questionnaire. Venous blood samples were collected during the first and third trimester after consent was obtained. Serum IgG and IgM antibodies (Abs) as well as IgG avidity were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
2
3
1
3
Order By: Relevance
“…Eighty percent of the participants had post-primary school education which suggests better understanding of hygiene principles. Similar to findings in this study, other studies have also reported the absence of associations between consumption of raw vegetables and T. gondii infection [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Eighty percent of the participants had post-primary school education which suggests better understanding of hygiene principles. Similar to findings in this study, other studies have also reported the absence of associations between consumption of raw vegetables and T. gondii infection [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies had reported that being rural dweller [ 41 ], having low education/illiterate [ 42 ], eating undercooked meat [ 43 ], cat ownership [ 39 , 40 ], drinking water from public sources [ 38 ], and being HIV positive [ 44 ] were all found to be risk factors for contracting T. gondii infection. However, none of these factors had significant association with T. gondii seropositivity in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, a slightly higher seroprevalence of 22% was reported in 2014 using ELISA [38]. Using the same method, 7.7% seropositivity was recently published in Taiwan [39], which is lower than that detected in the present study. However, the number of pregnant women tested was low, which is also a limitation of the current study.…”
Section: Discussioncontrasting
confidence: 50%
“…The level of education, as described in the literature, influences not only the knowledge but also the seroprevalence estimates to T. gondii : pregnant women with a lower level of education have higher seroprevalence estimate than those with higher schooling. Consequently, pregnant women with a higher educational level appear to have a more accurate knowledge of protozoan disease in order to prevent it [33].…”
Section: Discussionmentioning
confidence: 99%